2015
DOI: 10.1371/journal.pone.0142772
|View full text |Cite
|
Sign up to set email alerts
|

Are Dieting and Dietary Inadequacy a Second Hit in the Association with Polycystic Ovary Syndrome Severity?

Abstract: BackgroundThe composition of the diet is of increasing importance for the development and maturation of the ovarian follicles. In Polycystic Ovary Syndrome (PCOS) healthy dietary interventions improve the clinical spectrum. We hypothesized that dieting and diet inadequacy in the reproductive life course is associated with impaired programming of ovarian follicles and contributes to the severity of the PCOS phenotype.Methods and FindingsTo determine associations between the use of a self-initiated diet and diet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 49 publications
4
6
0
Order By: Relevance
“…Our study indicated that, despite significant differences in BMI and WHR, overall caloric intake and physical activity did not differ between women with and without PCOS, as have been observed in previous studies conducted in North America (Douglas et al, ; Wright et al, ). These findings demonstrate that obese women with PCOS are not in an energy surplus state supporting previous studies that suggest women with PCOS could indeed have an altered metabolism contributing to their obesity and IR (Georgopoulos et al, ; Huijgen et al, ; Robinson et al, ).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Our study indicated that, despite significant differences in BMI and WHR, overall caloric intake and physical activity did not differ between women with and without PCOS, as have been observed in previous studies conducted in North America (Douglas et al, ; Wright et al, ). These findings demonstrate that obese women with PCOS are not in an energy surplus state supporting previous studies that suggest women with PCOS could indeed have an altered metabolism contributing to their obesity and IR (Georgopoulos et al, ; Huijgen et al, ; Robinson et al, ).…”
Section: Discussionsupporting
confidence: 87%
“…2006; Wright et al, 2004). These findings demonstrate that obese women with PCOS are not in an energy surplus state supporting previous studies that suggest women with PCOS could indeed have an altered metabolism contributing to their obesity and IR (Georgopoulos et al, 2009;Huijgen et al, 2015;Robinson et al, 1992).…”
Section: Ta B L E 1 (Continued)supporting
confidence: 84%
“…Interestingly, androgens stimulate appetite, food craving and recurrent binge eating, although the underlying mechanisms are not understood [21,46,47]. In an explorative study, we observed that women with PCOS were frequently dieting, very often consuming substandard foodstuffs relative to that consumed by the control population [48]. These substandard diets were characterized by low serum folate and elevated homocysteine concentrations, indicating a more general derangement in 1C metabolism associated with a hyperandrogenic status in these women.…”
Section: Eating Disorders and Diet Compositionmentioning
confidence: 85%
“…Though speculative and requiring direct exploration in studies with more in-depth metabolic measures, women among this group may experience normal menstrual cycles and fecundability for the very reason that they maintain higher insulin sensitivity, protecting them from their underlying “PCOS potential.” Indeed, prior evidence indicated no association between polycystic ovarian morphology and glucose tolerance or insulin sensitivity, lending evidence to the distinction of ovarian/follicular dysfunction from the metabolic factors which may exacerbate, as opposed to cause, the pathology (29). It is logical to suspect that women in the group of highest T and AMH may be more likely to develop PCOS if exposed to insulin resistance brought on through diet, excess adiposity, or other exposures, akin to a ‘second hit’ as described previously for exacerbating PCOS severity (30). Alternatively, some women in the high T/high AMH group may meet criteria for clinical PCOS diagnosis, but have not received such a diagnosis.…”
Section: Discussionmentioning
confidence: 98%